ETHNOSCIENCE-BASED SCIENCE TEACHING AND LEARNING TO IMPROVE STUDENTS' COGNITIVE LEARNING OUTCOMES: A SYSTEMATIC LITERATURE REVIEW - Tjokorda Gde Putra Wirama; I Wayan Suja; I Nyoman Tika (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
This study addresses students’ low cognitive learning outcomes in natural science subjects caused by several factors, one of which is the students’ inadequacy to analyze and communicate different scientific topics. Ethnoscience-based science teaching and learning, with its direct observation, is therefore viewed as a suitable approach to address the problem as it engages students to identify scientific problems, explain phenomena scientifically, and draw conclusions. The goal of this study is to analyze the importance of the role of ethnoscience-based science teaching and learning in improving students' cognitive learning outcomes. The systematic literature review is selected as the research method. The process of data collection is done through collecting data from many different sources; they are articles and scientific journals indexed by Scopus and accredited journals sinta 1 and 2. The study findings indicate that the ethnoscience-based science teaching and learning improve students' creative and critical thinking skills, and thus increasing the students’ cognitive learning outcomes.